Multi-agent game analysis on standardized discretion of environmental administrative penalty - Ma, Xiaohong; Xin, Baogui; Wu, Gaobo (Frontiers in Environmental Science, 2023)
An environmental administrative penalty is a powerful tool to regulate environmental pollution and ecological destruction by punishing intentional violations. Still, unchecked discretion may lead to excessively low or high penalties, breaking our balance of desire for uniformity with the need for discretion. To achieve the balance, regulators may employ standardized discretion to achieve greater compliance by punishing intentional violations in a standardized way. However, policymakers and scholars have different attitudes on understanding whether standardized discretion helps enforcement. For this purpose, we construct a muti-agent dynamic game under the standardized discretion of environmental administrative penalty (SDEAP). The results show that: (i) SDEAP can positively affect firms' output and emission reduction efforts but negatively affect environmental quality; (ii) The lower limit of SDEAP can positively affect environmental quality but negatively affects firms' output and emission reduction efforts; (iii) The upper limit of SDEAP can positively affect firms' output, emission reduction efforts, and environmental quality; (iv) SDEAP can restrict law enforcement and improve firms' efforts to reduce emissions. This work can be helpful both to firms and the government as the basis for developing and implementing SDEAP.